Exploring the Role of Self-Efficacy in Antiretroviral Therapy Adherence Among HIV Patients in Regional General Hospital - Wahyuni, Ika Sri; Rondhianto; Riyanti, Rini; Rohkmah, Dewi; Suharsono (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the role of self-efficacy in antiretroviral therapy (ART) adherence among HIV patients at RSUD Blambangan Banyuwangi using a qualitative case study approach. Data were collected from 36 purposively sampled HIV patients through in-depth interviews, direct observation, and document analysis. Thematic analysis was conducted through data reduction, coding, categorization, and conclusion drawing, with validity ensured via triangulation, member checks, and prolonged engagement. Findings reveal that higher self-efficacy enhances ART adherence by fostering consistent medication routines, resilience, and proactive communication with healthcare providers. Emotional stability, family and peer support, and medical staff guidance were identified as key factors influencing self-efficacy. The study highlights the need to integrate psychological support and self-efficacy enhancement programs into HIV care services to improve treatment adherence.